THE EFFECT OF PROFITABILITY, LEVERAGE AND CAPITAL INTENSITY TO THE TAX AGGRESSIVENESS (LISTED PROPERTY AND REAL ESTATE COMPANIES IN INDONESIA STOCK EXCHANGE DURING 2011-2014) - admin, Zalfa Nurfiasri B42112013 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
This research aims to analyze the effect of profitability (ROA), leverage ,and capital intensity to the tax aggressiveness. Tax aggressiveness is dependentvariable and measured by using effective tax rate. Profitability (ROA), leverage,and capital intensity are independent variables in this research. This research wasconducted on property and real estate companies listed on Indonesia StockExchange (IDX) from 2011 to 2014. The sample was selected with purposivesampling method, where obtained 28 companies which meet the criteria. While thetotal of pooled data for four years from 2011 to 2014 is 112 samples (28x4). Thisresearch used classic assumption test, multiple regression analysis and hypothesistest to analyze the data. The results showed that profitability and leverage do nothave the same direction with effective tax rate, while capital intensity has the samedirection with effective tax rate. There are still many limitations and shortcomingsnamely the effect of independent variables on the dependent variable can onlyexplain by 5.4%. Hence, more independent variables are needed.Keywords : Profitability, Leverage, Capital Intensity, Effective Tax Rate, TaxAggressiveness